Autistic and Non-Autistic Experience of the Sensory Aspects of the Church Service - Unwin, Katy (Journal of psychology and theology, 2024)
Sensory differences in autism can impact many areas of life, including engagement in church. Fewer autistic people attend church than non-autistic people, with qualitative studies finding that the sensory experience is one reason for this. To date, no quantitative studies have investigated the impact of sensory aspects of the church service on autistic people. In this study, 299 participants from a range of denominations (autistic = 82; self-diagnosed autistic = 61; non-autistic = 156; aged 18–82 years) completed an online questionnaire about their sensory experience within the church. A principal components analysis (PCA) was conducted on the questionnaire data, establishing four statistically derived components, which were then compared between diagnostic groups. We found that autistic people experienced significantly more sensory barriers in church services (“Barriers” Component 1), received/required more accommodations (“Accommodations” Component 3), and felt more connected to God when they felt in control of the sensory and social aspects of the service (“Control” Component 4) than non-autistic people. All participants experienced similar enjoyment of some sensory aspects of the service (“Facilitators” Component 2). We also found evidence that the sensory environment can make attending church difficult, or even limit attendance, in our autistic sample. Recommendations for supporting autistic attendance at, and engagement in, church are made.